2021
DOI: 10.7150/jca.55570
|View full text |Cite
|
Sign up to set email alerts
|

Upregulating KTN1 promotes Hepatocellular Carcinoma progression

Abstract: Background: Hepatocellular carcinoma (HCC) presents a common malignant tumor worldwide. Although kinectin 1 (KTN1) is the most frequently identified antigen in HCC tissues, the detailed roles of KTN1 in HCC remain unknown. This study seeks to clarify the expression status and clinical value of KTN1 in HCC and to explore the complicated biological functions of KTN1 and its underlying mechanisms. Methods: In-house reverse transcription quantitative polymerase chain reaction (RT-qPCR) was used to detect the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The KTN1 gene, a member of the kinectin protein family, primarily localizes in the ER membrane and plays a key role in encoding an integral membrane protein and regulating the localization and distribution of the ER (Zheng et al, 2022). Previously, research on KTN1 focused on cancer occurrence (Li, Li, et al, 2021; Pan et al, 2021). In breast cancer, the KTN1 protein activated the NF‐κB signaling pathway, which is also intensely associated with the occurrence of pulmonary fibrosis (Gao et al, 2021; Wei et al, 2023; Zhang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The KTN1 gene, a member of the kinectin protein family, primarily localizes in the ER membrane and plays a key role in encoding an integral membrane protein and regulating the localization and distribution of the ER (Zheng et al, 2022). Previously, research on KTN1 focused on cancer occurrence (Li, Li, et al, 2021; Pan et al, 2021). In breast cancer, the KTN1 protein activated the NF‐κB signaling pathway, which is also intensely associated with the occurrence of pulmonary fibrosis (Gao et al, 2021; Wei et al, 2023; Zhang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…As a kinectin, KTN1 has been reported to promote hepatocellular carcinoma progression and the growth of triple-negative breast cancer. 44 , 45 In 2021, Zhenhua Ding and his colleagues made a breakthrough in their study on KTN1 function. They found that KTN1 stabilized the protein expression level of EGFR by decreasing its ubiquitination, 46 suggesting that the MALAT1-KTN1-EGFR axis promoted the development of cutaneous squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%